2002
DOI: 10.1002/cncr.10739
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor and social support in patients with ovarian carcinoma

Abstract: BACKGROUND The modulation of immunologic activities relevant to cancer by behavioral factors, such as stress, depression, and social support, is well documented. However, associations of behavioral factors with cytokines involved in tumor angiogenesis have not been studied. Vascular endothelial growth factor (VEGF) is a key cytokine that is capable of stimulating tumor angiogenesis, and it has been associated with poorer survival in patients with ovarian carcinoma. VEGF is modulated by a variety of behaviorall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 65 publications
(78 reference statements)
5
104
0
3
Order By: Relevance
“…36 We have previously reported that higher levels of social support were correlated with lower VEGF levels in serum from presurgical patients with ovarian carcinoma providing a possible mechanism by which poor social support may be associated with disease progression. 37 We have also demonstrated that VEGF production by ovarian cancer cell lines was enhanced by stress hormones such as norepinephrine, epinephrine, and isoproterenol in vitro and blocked by the b-antagonist propranolol. 38 Based on our previous studies, we sought to elucidate whether chronic stress and the associated increase in sympathetic nervous system activity had a causal effect on growth and metastasis of ovarian cancer in vivo.…”
Section: Neuroendocrine Influences On Cancermentioning
confidence: 79%
“…36 We have previously reported that higher levels of social support were correlated with lower VEGF levels in serum from presurgical patients with ovarian carcinoma providing a possible mechanism by which poor social support may be associated with disease progression. 37 We have also demonstrated that VEGF production by ovarian cancer cell lines was enhanced by stress hormones such as norepinephrine, epinephrine, and isoproterenol in vitro and blocked by the b-antagonist propranolol. 38 Based on our previous studies, we sought to elucidate whether chronic stress and the associated increase in sympathetic nervous system activity had a causal effect on growth and metastasis of ovarian cancer in vivo.…”
Section: Neuroendocrine Influences On Cancermentioning
confidence: 79%
“…The relationship between levels of distress and immune factors was assessed in three good studies [18,23,24]. Costanzo et al [18] found that a history of depression and increased depressed mood were associated with higher levels of interleukin-6 in ascitic fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Costanzo et al [18] found that a history of depression and increased depressed mood were associated with higher levels of interleukin-6 in ascitic fluid. Lutgendorf et al [23] found that higher levels of helplessness were associated with higher levels of vascular endothelial growth factor, a pro-angiogenic factor, which is associated with poorer survival. Lutgendorf et al [24] found that increased levels of distress were associated with lower levels of natural killer cells in tumour-infiltrating lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…A continuous infusion of propranolol abrogated the effects of stress on tumor burden and pattern of disease; therefore, confirming the importance of beta-adrenergic receptors on ovarian cancer cells in an in vivo model. Clinical studies have also shown a correlation between higher levels of social support and lower serum VEGF levels in ovarian cancer patients [47].…”
Section: Angiogenesismentioning
confidence: 98%